Herbert Block papers - Block, Herbert, 1909-2001.; Block, Herbert, 1909-2001.
Correspondence, writings, speeches, interviews, clippings, cartoon reprints, and printed material relating chiefly to Block's career as the political cartoonist "Herblock" for the Washington Post and as author of several books. Also documents his work with the Chicago Daily News and the Newspaper Enterprise Association in Cleveland, and his U.S. Army service. Subjects include cartooning, politics, social activities among Washington's political and cultural circles, and personal affairs. Includes research material for and drafts of his memoirs, Herblock: A Cartoonist's Life (1993) and transcript of an interview conducted by Katharine Graham with Block in 1990.
Correspondents include Tony Auth, Alan Barth, Frederick G. Blumenthal, Benjamin C. Bradlee, Milton Arthur Caniff, Bill Clinton, Irving Dilliard, Tom Engelhardt, W. H. Ferry, John R. Fischetti, Gerald R. Ford, William E. Gold, Donald E. Graham, Katharine Graham, Philip L. Graham, Draper Hill, Irving Hoffman, Lyndon B. Johnson, Lynn Franks Johnston, Chuck Jones, Walt Kelly, Anthony Lewis, Jeff MacNelly, Wesley McCune, Agnes Elizabeth Ernst Meyer, Eugene Meyer, Robert Chesley Osborn, Walt Partymiller, Charles Peters, Joseph L. Rauh, Maurice Rosenblatt, Roger Rosenblatt, Vaughn Shoemaker, Ann Telnaes, and Harry S. Truman.
Library of Congress Prints and Photographs Division.
Political cartoonist, author, and journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Auth, Tony -- Correspondence; Barth, Alan -- Correspondence; Blumenthal, Frederick G. -- Correspondence; Bradlee, Benjamin C. -- Correspondence; Caniff, Milton Arthur, -- 1907-1998 -- Correspondence; Clinton, Bill, -- 1946- -- Correspondence; Dilliard, Irving, -- 1904-2002 -- Correspondence; Engelhardt, Tom, -- 1944- -- Correspondence; Ferry, W. H. -- Correspondence; Fischetti, John R. -- Correspondence; Ford, Gerald R., -- 1913-2006 -- Correspondence; Gold, William E. -- Correspondence; Graham, Donald E., -- 1945- -- Correspondence; Graham, Katharine, -- 1917-2001 -- Correspondence; Graham, Philip L., -- 1915-1963 -- Correspondence; Hill, Draper -- Correspondence; Hoffman, Irving, -- 1909-1968 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Johnston, Lynn Franks, -- 1947- -- Correspondence; Jones, Chuck, -- 1912-2002 -- Correspondence; Kelly, Walt -- Correspondence; Lewis, Anthony, -- 1927-2013 -- Correspondence; MacNelly, Jeff -- Correspondence; McCune, Wesley, -- 1918- -- Correspondence; Meyer, Agnes Elizabeth Ernst, -- 1887-1970 -- Correspondence; Meyer, Eugene, -- 1875-1959 -- Correspondence; Osborn, Robert Chesley, -- 1904- -- Correspondence; Partymiller, Walt, -- 1911-1991 -- Correspondence; Peters, Charles, -- 1926- -- Correspondence; Rauh, Joseph L., -- 1911- -- Correspondence; Rosenblatt, Maurice -- Correspondence; Rosenblatt, Roger -- Correspondence; Shoemaker, Vaughn, -- 1902- -- Correspondence; Telnaes, Ann, -- 1960- -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; United States. -- Army; Newspaper Enterprise Association; Chicago daily news; Washington post; American newspapers -- Illinois -- Chicago; American newspapers -- Ohio -- Cleveland; American newspapers -- Washington (D.C.); Authors; Cartoonists; Journalists